Articulações entre governo local e sociedade civil em torno do desenvolvimento da pesca artesanal: estudo de caso no município de Ubatuba-SP - Ribeiro, Gabriel Martim Jacintho (2017)
Despite being one of the oldest activities carried out by man and having an enormous socioeconomic importance for Brazil, fishing industry, mainly the small-scale fisheries, is still quite neglected from national political processes. Following the country's agro-export vein, the federal government's growing orientation towards increasing production through aquaculture and industrial fishing seems to be an incompatible strategy, both with the characteristics of the natural reproductive forces of the South Atlantic Ocean (in which the brazilian coast is situated) and with the social reality of the fisheries sector, which employs almost 1 million workers (more than 90% working in small-scale fisheries). The disorderly institutionalization of a national plan for the fishing industry is reflected in the other federative entities. As an economic activity, of an extractive nature, and carried out in public domain territory, marine capture fisheries are pressured (i) economically - by competition with industrial fisheries; and (ii) territorially - by other economic activities at sea, by the impacts of increasing coastal urbanization and by the rules and laws imposed by environmental conservation agencies, at different levels of the federation. Recent, but scarce, studies seek to understand, punctually, the effects of certain public policies, or comanagement systems, with a view from the territory where the activity occurs. However, it is understood that looking at the development of small-scale fisheries should also consider the economic, environmental and social dimensions, but mainly incorporate a better understanding of the forces acting in the local context. In order to contribute to this discussion, and incorporating the political dimension, the research question that guided this dissertation was: How the processes of interaction between different social groups (government and civil society), in a local context, influence the development of small-scale fisheries? In order to answer it, a bibliographical review was made respecting the contributions, among others, from the fields of sociology, anthropology, economics, agronomy and sustainable development. There was also a historical reconstitution of the federal institutionalization around fisheries industry, a characterization of the small-scale fisheries sector and the main policies and instances of participation for the sector. From this point, was adopted the critical-constructivist theoretical model proposed by Pozzebon et al. (2009) in order to deepend into the case study chosen: the municipality of Ubatuba-SP. The research findings point to the issue around the configuration of Brazilian federalism as an obstacle to the creation, implementation and coordination of policies for the sector, which also weakens the institutional arrangements in a subnational context. Thus, the integration of local actors is hampered by a dependence on federal policies to subsidize and organize the activity. It is also noted that the experiences of political decentralization around the coastal planning and the shared management of the marine environment, by the way they were implemented and by their consultative character in which the final decisions are in the hand of the State of São Paulo, do not seem sufficiently capable of strengthen small-scale fisheries locally.